2014
DOI: 10.1007/s10508-014-0299-x
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Reactions to Hooking Up Among U.S. University Students

Abstract: Hooking up is defined as a physical encounter between two people who are not romantically committed. This study explored whether there were subgroups of young adults with unique reactions to hooking up (N = 879). Psychosocial predictor variables (gender, depression, loneliness, intoxication level, college adjustment, and hope for a committed relationship) were investigated along with emotional reactions as the outcome variables. Through the use of cluster analysis, four distinct clusters were identified: Happy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 29 publications
1
18
0
Order By: Relevance
“…For example, some research that used college-based samples found that casual sex was correlated with decreased well-being and higher psychological distress, substance use, and depressive symptoms (Bersamin et al, 2014; Fielder & Carey, 2010a; Grello et al, 2006). Other research that used college students reported that casual sex was not always associated with negative emotional and social ramifications (Strokoff, Owen, & Fincham, 2015). In fact, college students claimed more positive emotional consequences of hooking up compared to negative ramifications (Snapp, Ryu, & Kerr, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, some research that used college-based samples found that casual sex was correlated with decreased well-being and higher psychological distress, substance use, and depressive symptoms (Bersamin et al, 2014; Fielder & Carey, 2010a; Grello et al, 2006). Other research that used college students reported that casual sex was not always associated with negative emotional and social ramifications (Strokoff, Owen, & Fincham, 2015). In fact, college students claimed more positive emotional consequences of hooking up compared to negative ramifications (Snapp, Ryu, & Kerr, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research on emotional consequences of different sexual behaviors often focuses on short-term consequences, which may be a mechanism through which behaviors influence longer term mental health and well-being (Strokoff, Owen, & Fincham, 2014; Vasilenko, Lefkowitz, & Welsh, 2014). Research on short-term consequences of sexual behavior distinguishes between the valence of consequences (positive versus negative), and whether consequences are intrapersonal or interpersonal (Campbell, 2008; Vasilenko et al, 2012).…”
Section: Emotional Consequences Of Sexual Behaviorsmentioning
confidence: 99%
“…Recent research suggests that approximately 60% to 81% of college students report having engaged in some form of hooking up (Bachtel, 2013; Fielder & Carey, 2010). While most college students report hooking up to be a positive experience (Lewis, Granato, Blayney, Lostutter, & Kilmer, 2012; Owen & Fincham, 2011; Owen, Quirk, & Fincham, 2014; Plante, 2014; Strokoff, Owen, & Fincham, 2015), some students do experience negative consequences (Napper, Montes, Kenney, & LaBrie, 2015). For example, in a study on the negative impacts of hooking among undergraduate students, 77.4% of students reported experiencing at least one negative hookup consequence in the past three months in a sample that was representative of both male and female college students (Napper et al, 2015).…”
mentioning
confidence: 99%